Catalytic Epoxidation of Waste Palm Cooking Oil Using In Situ Generated Peracid and a Hybrid Catalyst System - Mohd Jumain Jalil (Kemija u Industriji, 2025)
This study investigates the catalytic epoxidation of waste palm cooking oil via an in situ generated peracid mechanism, employing a hybrid homogeneous catalyst system comprising sulphuric and nitric acid to enhance efficiency and sustainability. The research focuses on optimising key reaction parameters, which include temperature, catalyst loading, hydrogen peroxide-to-oleic acid molar ratio, and formic acid-to-oleic acid molar ratio. The optimised conditions identified were: (1) reaction temperature of 65 °C, yielding the highest oxirane content while minimising side reactions; (2) a catalyst loading of 0.5, achieving the best balance of conversion efficiency and reaction stability; (3) a hydrogen peroxide-to-oleic acid molar ratio of 2 : 1, maximising oxirane yield without promoting degradation reactions; and (4) a formic acid-to-oleic acid molar ratio of 1 : 1, providing the optimal acid concentration for efficient epoxidation. These findings support the potential of using waste-derived oils in biopolymer production, aligning with sustainable development and circular economy principles. This optimised approach enhances waste valorisation and contributes to the synthesis of eco-friendly materials.